2019
DOI: 10.1186/s12864-019-5711-4
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal imbalance in pigs showing a syndromic form of cleft palate

Abstract: Background Palatoschisis or cleft palate is a known anomaly in pigs resulting in their death. However, little is known about its aetiology. A detailed description of the phenotype was derived from necropsy and by computed tomography revealing that all 20 cases also exhibited hypodontia and renal cysts. Furthermore, a genetic origin was assumed due to dominant inheritance as all 20 recorded cases were confirmed offspring of a single boar. Results Single nucleotide varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…It is certainly easier to obtain DNA material for sequencing than to perform chromosome staining with laborious analysis of lymphocyte cultures. Furthermore, sequence data provides an enormous amount of additional genomic information besides large karyotype defects, because it is possible to detect recessive lethal alleles (23), de novo events and smaller structural variation events (5), as well as SNP and InDels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is certainly easier to obtain DNA material for sequencing than to perform chromosome staining with laborious analysis of lymphocyte cultures. Furthermore, sequence data provides an enormous amount of additional genomic information besides large karyotype defects, because it is possible to detect recessive lethal alleles (23), de novo events and smaller structural variation events (5), as well as SNP and InDels.…”
Section: Discussionmentioning
confidence: 99%
“…In general, sequence reads will not only enable detection of RTs, but also enhance re nement of the location of the breakpoints and detailed description of the breaks and junctions. In pigs, Grahofer et al (5) have successfully re ned the breakpoint location of an segregating RT causing malformed piglets using sequence data of an unbalanced and balanced sib. Donaldson et al (18) showed that translocation breakpoints are nonrandomly distributed across cytogenetic bands, they are more prevalent on longer cytogenetic bands, gram negative bands, and common fragile sites.…”
Section: Introductionmentioning
confidence: 99%
“…3 one of the lter criteria for the detected inter-chromosomal translocations was the presence of a matching pair, hence between brackets are the number of reciprocal pairs, i.e. the actual number of possible RTs Strict ltering: Basic ltering: Pass DELLY quality lter and precise position; nal ltering: mapping quality = 60, at least 10 split reads supporting the translocation, ≤ 60 discordant paired end reads, consensus alignment quality > 0.9, and matching second translocation with matching connection type present 2 Relaxed ltering: Translocations that failed the quality lter of DELLY (LowQual instead of PASS; basic ltering) and with 5 or more split reads supporting the translocation ( nal ltering) were retained. 3 one of the lter criteria for the detected inter-chromosomal translocations was the presence of a matching pair, hence between brackets are the number of reciprocal pairs, i.e.…”
Section: Reducing Sequencing Coveragementioning
confidence: 99%
“…Heterozygous individuals carrying a balanced RT produce three type of gametes: unbalanced gametes, balanced RT carrying gametes, and normal gametes. The unbalanced gametes give rise to embryos carrying partial monosomy and trisomy, which are mostly lethal or result in severely malformed piglets (1)(2)(3). Carriers of balanced RTs tend to be hypoproli c individuals with a reduction in litter size of approximately 36-39% (1,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation